(3JYQjaGJ MOhO GdYdhes - (3RcQjG Hf eMeO Hf CMeO Hf RcQjG GdCfUGQj GdSfjcj GdeUQj GdTGaYqj, CHh jMji , J (B926 (3g` s
(3ChdgG (B:s
(3hHYO agPg QSGdI eTJedI Ydi HjGf TQhW JYdje GdYdhe hJYdegG GdeSWQg hYdi MUQ CfhYgG s
(3BNQgG (B:s
(3agPg MOhO hehVhYGJ hZGjGJ YTQjf YdekG bO SeM GdhbJ HJSWjQgG Ydi gPG GdfeW GdeSQhO s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B46 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B4 - (3U (B182 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B374s
(3eUOQ GbJfGA GdCUd (B:s
(3GdecJHI GdeQcRjI GdYGeI (B_ (3GdehUd (B(306(3L(B) s
Keywords: (3GdeYGQa GdYGeIs